2021
DOI: 10.1136/bmjopen-2021-056203
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of dry eye in the USA: a systematic review protocol

Abstract: IntroductionDry eye is a multifactorial chronic condition characterised by tear film insufficiency and instability, and ocular symptoms including foreign body sensation, itching, irritation, soreness and visual disturbance. The prevalence and incidence of dry eye are major determinants of the magnitude of economic and societal costs of the disease. This protocol proposes a systematic review and meta-analysis of the prevalence and incidence of dry eye in the USA.Methods and analysisWorking with an information s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…We registered the review prospectively on PROSPERO (CRD42021256934) and reported it in accordance with the Meta-analysis of Observational Studies in Epidemiology (MOOSE) and the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines . We followed the methods established in the published protocol …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We registered the review prospectively on PROSPERO (CRD42021256934) and reported it in accordance with the Meta-analysis of Observational Studies in Epidemiology (MOOSE) and the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines . We followed the methods established in the published protocol …”
Section: Methodsmentioning
confidence: 99%
“…We were unable to cross-walk prevalence from studies with diverse definitions because we did not find a methodologically robust study with a satisfactory reference standard to demonstrate the bias associated with each definition . We could not perform meta-regression on geo-environmental variables (eg, latitude, humidity) because of the lack of reported data …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of Face Mask-Related Ocular Surface Modi cations, the Ocular Surface Disease Index (OSDI) score was abnormal in more than half of the cases [14].…”
mentioning
confidence: 99%